2020
DOI: 10.38007/kme.2020.010404
|View full text |Cite
|
Sign up to set email alerts
|

New Energy Vehicle System Optimization on Hill Climbing Algorithm

Abstract: New energy vehicles(NEV) include three major categories: hybrid vehicles, fuel cell vehicles, and pure electric vehicles. Pure electric vehicles are vehicles that completely use the electrical energy from the on-board battery pack as the driving energy for vehicle driving. The battery pack on pure electric vehicles can use renewable energy to replace traditional fuel, which can not only alleviate the current energy crisis, but also greatly reduce the environmental pollution caused by the automotive industry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This article selects five listed companies among BYD's core suppliers, namely Fuyao Glass Industry Group Co., Ltd., Shenyin Baoshan New Technology Co., Ltd., Huizhou Desai Xiwei Automotive Electronics Co., Ltd., Landai Technology Group Co., Ltd., and iFlytek Technology Co., Ltd. From Table 4, it can be seen that the accounts receivable turnover rate of BYD suppliers has significantly increased and shows an upward trend from 2018 to 2020. Therefore, it can be concluded that the implementation of the "DiChain" supply chain finance platform has enabled BYD's suppliers to obtain more loans, thereby improving their operational efficiency [11][12][13].…”
Section: Analysis Of the Effect Of "Di Chain" On Improving Byd's Oper...mentioning
confidence: 99%
“…This article selects five listed companies among BYD's core suppliers, namely Fuyao Glass Industry Group Co., Ltd., Shenyin Baoshan New Technology Co., Ltd., Huizhou Desai Xiwei Automotive Electronics Co., Ltd., Landai Technology Group Co., Ltd., and iFlytek Technology Co., Ltd. From Table 4, it can be seen that the accounts receivable turnover rate of BYD suppliers has significantly increased and shows an upward trend from 2018 to 2020. Therefore, it can be concluded that the implementation of the "DiChain" supply chain finance platform has enabled BYD's suppliers to obtain more loans, thereby improving their operational efficiency [11][12][13].…”
Section: Analysis Of the Effect Of "Di Chain" On Improving Byd's Oper...mentioning
confidence: 99%